Study of Sanitation Infrastructure Operations (Case Study: Wastewater Infrastructure in Ciamis Regency) - Maulana, Suhenra (Engineering, MAthematics and Computer Science Journal (EMACS), 2024)
Sanitation infrastructure is intended to complement the needs of people who do not yet have access to wastewater infrasctucture include bathing, washing and toilet. Inadequate sanitation infrastructure in an area can cause problems of decreasing environmental quality in residential areas. Based on data from Ciamis Regency in Figures for 2022, it is stated that the population growth rate is 0.94%, this is one of the problems arising from the rapid population growth and various activities carried out, especially sanitation issues, which are related to domestic wastewater treatment including bathing, washing and toilet bathing facilities or Mandi, Cuci, Kakus (MCK). Ciamis Regency has a total of 63 MCKs that have been built in the 2010-2022 period, spread across 19 sub-districts and 62 villages with 63 MCK units. The results of the assessment of the functioning of the MCK infrastructure in Ciamis Regency show that 37 MCK units are in prime condition, 23 MCK units are damaged but can still function properly, 3 MCK units where users are hesitant to use the MCK. Efforts need to be made to repair damaged and/or non-functioning MCKs by increasing participation from the user community in the form of contributions to MCK managers. This is with the aim that people want to reuse and care for MCK as a form of sense of ownership and shared responsibility.